2006
DOI: 10.1108/13665620610682107
|View full text |Cite
|
Sign up to set email alerts
|

Individual learning accounts: a strategy for lifelong learning?

Abstract: Learning strategies are immensely ambiguous phenomena and nothing is clear-cut about them. zoltan Dőrnyei The object of education is to prepare the young to educate themselves throughout their lives. Robert M. Hutchins The paper examines how the language learning strategies that learners prefer in learning professional language at tertiary level can be used for lifelong education. It is well known that in language learning students apply various learning strategies, yet not all learners are equally successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 9 publications
4
30
0
1
Order By: Relevance
“…The potential to grow within a job or an organisation is also related positively to employees' intentions to learn (Raemdonck 2006). In the profit sector, the support within the working environment was positively correlated with the learning intentions of low-qualified employees (Colquitt et al 2000;Eisenberger et al 2002;Hazelzet et al 2009;Maurer and Tarulli 1994;Noe et al 1990;Renkema 2006). Tharenou (1997) confirmed the hypothesis that participation in training and developmental activities is linked to the perception of how supportive an organisation is towards learning and development.…”
Section: Characteristics Of the Social Context And Its Actors (Macro-supporting
confidence: 73%
See 3 more Smart Citations
“…The potential to grow within a job or an organisation is also related positively to employees' intentions to learn (Raemdonck 2006). In the profit sector, the support within the working environment was positively correlated with the learning intentions of low-qualified employees (Colquitt et al 2000;Eisenberger et al 2002;Hazelzet et al 2009;Maurer and Tarulli 1994;Noe et al 1990;Renkema 2006). Tharenou (1997) confirmed the hypothesis that participation in training and developmental activities is linked to the perception of how supportive an organisation is towards learning and development.…”
Section: Characteristics Of the Social Context And Its Actors (Macro-supporting
confidence: 73%
“…Research has shown that participation in previous learning activities yields a positive correlation with learning intention (Raemdonck 2006;Renkema 2006). Moreover, the more positively a course was evaluated, the more inclined participants were to take up courses in the future (Renkema 2006). The attitude of employees towards learning activities has been shown to be strong predictors of their learning intention (Maurer et al 2003;Noe and Wilk 1993;Renkema et al 2009).…”
Section: Characteristics Regarding Learning Education and Trainingmentioning
confidence: 94%
See 2 more Smart Citations
“…As a consequence, if KSAs associated with other disciplines are not factored into their 1980;Ajzen, 1991;Kim & Hunter, 1993;Maurer, Weiss, & Barbeite, 2003). Several researchers have also found a positive relationship between employees' prior participation in learning activities and their learning intentions (e.g., Bates, 2001;Kyndt, Govaerts, Dochy, & Baert, 2011;Maurer et al, 2003;Renkema, 2006). The relationship between actual participation in learning activities and learning intention appears to be reciprocal in nature (Kyndt, Onghena, Smet, & Dochy, 2014).…”
mentioning
confidence: 99%